Unrest index for estimating thermal comfort of poultry birds (Gallus gallus domesticus) using computer vision techniques - Del Valle, José Eduardo [UNESP]; Pereira, Danilo Florentino [UNESP]; Mollo Neto, Mario [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Salgado, Douglas D'Alessandro [UNESP] (Elsevier, 2021)
Behaviour can be used to infer animal welfare states. Poultry birds tend to move less under conditions of thermal stress; hence the hypothesis of this research is that this unrest behaviour can be used as an indicator of thermal comfort. The objective was to develop an Unrest Index for poultry bird's sensitive to changes in this behaviour under different air temperature conditions. The proposed Unrest Index was based on the Hausdorff distance measure and was tested on recorded videos of laying hens and broilers breeders, obtained in different experiments. The index was efficient in detecting the unrest of poultry birds in different thermal conditions and, in conditions above thermoneutrality, the birds moved significantly less. The distribution Unrest Index of data for each thermal condition tested was shown to be asymmetric. However, there seems to be a tendency to reverse this asymmetry when the conditions are thermal comfort and heat stress. It is suggested that the Unrest Index can be used to estimate the thermal comfort of poultry birds and that further studies on the asymmetry of the index data should be carried out in order to identify of the thermoneutrality zone of birds in a non-invasive way. The Unrest Index and the computer vision techniques adopted to assess poultry thermal comfort automatically were efficient in demonstrating differences in bird agitation in distinct thermal stress conditions. The low computational effort and the mathematical simplicity of the model allows the Unrest Index to incorporate bird surveillance systems and estimate thermal comfort automatically.
Keywords: Animal behaviour; Comfort index; Hausdorff distance; Image analysis; Precision livestock farming